Relationship between job stress and staff performance in National Examination Council, Ilorin, Kwara State - Oladimeji, M. Rasheedat; Odefunsho, A. Olukayode; Akaje, O. Husseinat (Kashere Journal of Education, 2023)
This study investigated the relationship between job stress and staff performance in National Examination Council, Ilorin Kwara State. The data collected from the respondents were statically analyzed with both descriptive and inferential statistics. Frequency counts, tabulations, percentage, mean, standard deviation and Pearson Product Moment Correlation (PPMC) statistics were used to test the research hypotheses at 0.05 level of significance. Descriptive survey design was adopted, employing questionnaire as an instrument for data collection through survey monkey. The research was carried out in National Examination Council (NECO), Ilorin Kwara State. The population of the study was the 96 NECO staff in Ilorin office. This resulted to 96 staff were sampled across all the 24 units. The researcher designed structured questionnaires titled: “Job Stress Assessment Questionnaire” (JSAQ) and “Staff Job Performance Assessment Questionnaire” (SJPAQ) were used to elicit information from the 96 respondents. The reliability measurement of the instruments was carried out through test re-test method. The results of the analysis in the research hypotheses revealed that; there was a significant relationship between level of stress and staff job performance at the National Examinations Council, Ilorin. The finding on the hypothesis (Ho2) which was rejected and the findings shows that there was a significant relationship between strategies for managing stress and staff job performance at the National Examinations Council, Ilorin. Based on the hypothesis on significant relationship between consequential effects of stress and staff job performance at the National Examinations Council, Ilorin, it was discovered that a significant relationship existed between consequential effects of stress and staff job performance at the National Examinations Council, Ilorin. The following were therefore; the organization should develop stress coping strategies in order to enhance staff job performance. Workshop and seminars should be organized for staff of National Examinations Councils on stress management techniques. This will enable the staff to put in their best in the performance of their job. The organization should identify those factors that are responsible for stress and devise means of reducing them to the barest minimum in order to enhance high productivity among staff. Specialization should be given prominence in the distribution of works to staff so that tasks assigned to them can be easily completed thereby reducing stress that may arise from job performance.